Documentos da família Vieira Ravasco (XVII-XVIII): edição semidiplomática e elementos para uma descrição da concordância verbal - Santos, Emília Carneiro dos (2022)
The present work presents documents from the 17th and 18th centuries, writings by two generations of the Vieira Ravasco family, who are of wid importance for studies on the genesis of Brazilian Portuguese Cult or socially prestigious norms. The development of this research is based on the three work agendas adopted by the Program for the History of Brazilian Portuguese (PHPB), of which the project Corpus Eletrônico de Documents Históricos do Sertão (CE-DOHS), to which the present research is linked, is a partner, namely: the historical-philological one; the socio-historical; linguistic-grammatical (CASTILHO, 2019). Thus, the semidiplomatic transcription of the manuscripts was carried out — following the rules for transcribing handwritten and printed documents from PHPB (CASTILHO, 2020) — and their paleographic description, the socio-historical contextualization of the documents and the descriptive study of verbal agreement. With the semi-diplomatic transcription, the main result is the availability of the edition for researchers who are dedicated to studying the most remote periods of BP; the socio-historical study contributes to the understanding of the historical and linguistic formation of BP and colonial Bahia; with the descriptive study of verb agreement, the results achieved contribute to morphosyntatically characterize the Portuguese written by educated people, born in Brazil during the colonial period. The present Dissertation collaborates with Phase 2 of the CE-DOHS project, which goes back to the Brazilian colonial period, in view of the socially prestigious norms and the socially stigmatized norms; this Master's research aims to bring data for the social and linguistic reconstruction of those norms.